Geomorphological and hydrological changes induced by the April 22, 1991 Limón, Costa Rica earthquake (Mw 7.7) - Barrantes, Gustavo (2021)
The Limón Earthquake induced changes in external geodynamics processes such as: crustal uplift, soil liquefaction, land settlement and slope instability. This research focuses on the hydrological and geomorphological changes. The methodology followed starts from field observation, landslide mapping, concentration of solid materials, and comparative analysis of satellite images and aerial photographs. It was determined that around 140 km2 of vegetation cover were destroyed, which intensified surface runoff and soil erosion. Approximately 210 million m3 of solid materials were transported by fluvial systems. These processes affected the upper and middle basins first and then the alluvial fans at the foothills, with the accumulation of sediments and subsequently their removal downstream, which produced an accelerated progradation process between 1992 and 1998.